Peranan Internal Auditing Dan Pengendalian Internal Dalam Meningkatkan Kinerja Perusahaan PT. Berkah Djamal Perbaungan - Enika Diana Batubara; Yenni Ramadhani Harahap; Sri Hartini; Muhammad Nursidin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The role of internal auditing is quite important in companies and influences internal control in improving company performance if it is carried out according to procedures and provisions of applicable professional standards. Company performance has an understanding as the result of a management activity in a company. In this study aims to analyze the role of internal auditing and internal control in improving company performance. The data used is primary data. This primary data was obtained from the results of the respondents' answers to the questionnaire which was distributed to 30 staff of PT. Blessings of Djamal Perbaungan. The results on the t test, the significant value of the role of internal auditing is 0.364 which means it is greater than 0.05. This explains that the role of internal audit has no significant effect on company performance. The significant value of internal control of 0.000 is less than 0.05, meaning that internal control has a significant effect on company performance, but the results of the F test in this study obtained a significant value of 0.000, meaning less than 0.05. This explains that the role of internal auditing and internal control has a significant effect on company performance. While the internal audit at PT. Berkah Djamal Perbaungan has played a role in accordance with the internal auditing role criteria and based on testing the respondents stated that they strongly agree that one of the obstacles lies only in the lack of internal audit training. Every company is advised to implement an internal control system and internal audit, so that every activity that occurs in the company can be controlled with the goals set and the performance of the company can be increased.